Development of gantry-based UTAR Hospital linen tracking through RFID using python - Fong, Karr Keet (2023)
In this project, I will propose and construct a gantry-based UTAR Hospital Linen Tracking through RFID using Python in order to minimize the workload of the hospital staff, boost the efficiency of the linen tracking system, and save money by reducing the loss of linen. The gantry-based RFID linen tracking system comprises a few components, like antenna, RFID tags, RFID gantry, and a back-end system to enable users to monitor the data uploaded to the cloud. The proposed system traces and monitors incoming and outsourcing linen from UTAR hospital and the laundry plant suppliers. Linen included are pillowcases, blankets, bedsheets, patient garments, surgical drapes, aprons, surgical caps, cleaning clothes, etc. As the linen products embedded with the RFID tag are scanned by the RFID reader or RFID gantry, unique identifications of the tags will be identified, and their location and allocation procedure will be stored in the cloud database. As a result, hospital staff may trace all the linens by accessing the cloud database record system on the industrial panel provided. I have used a dedicated Python integrated development environment (IDE), PostgreSQL, an open-source database, and Microsoft Power BI dashboard as the software for this project.